Research on the Road Network Design Optimization Based on SA-Apriori Analysis Considering RTAs - Jiao Li; Shuyan Su; Tianjie Zhang; Zelin Liu (IEEE Access)
Identifying the factors that affect road traffic accidents (RTAs) is an important prerequisite for preventing and managing traffic accidents. To enhance risk assessment of RTAs, especially prevention of major RTAs, a segment analysis (SA)-Apriori with Geo-spatial information of RTAs model was proposed to explore relevance between spatial structure features and RTAs rates & types. The variables such as Kernel, integration, choice with association rule indicators (support, confidence, lift) in Dadukou District of Chongqing as study area are used to measure correlations between RTAs and road spatial characteristics. Results show that the high global integration and high global choice of roads are positively correlated with the RTAs rates, no significant correlation between the occurrence of minor accidents and space structure features, a positive correlation between high & medium global choice and major RTAs. The results can provide reference for the prevention and management of urban RTAs, to reduce the accident rate and reduce the loss caused by accidents.